UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI DENGAN MENGGUNAKAN METODE PEMBELAJARAN (GQGA)GIVING QUESTION AND GETTING ANSWER DI SMA NEGERI 1 MUARA BATANG GADIS - Ela Andriani; Melvariani Syari Batubara (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
The problem in this research is the low student learning outcomes. The type of study is class action research. The Learning Model used is (GQGA) Giving Question And Getting Answer. The subject of this study is a student of grade X SMA Negeri 1 Muara Batang Gadis consisting of 21 students. The technique and Data collector tools are tests and observations. The results of the study can be seen from the student study results test at Cycle I with an average value of 62%, in cycle II to 76% with an increase of 14%. Then the students ' biological learning activities increased, it obtained from a percentage of 53% cycle I, and 73% in cycle II. So the increase of 20%. Keywords: Giving Question And Getting Answer, learning outcomes, learning activities